Effect of Span 60 on the Microstructure, Crystallization Kinetics, and Mechanical Properties of Stearic Acid Oleogels: An In‐Depth Analysis. Issue 2 (16th December 2015) - Uvanesh, K.; Sagiri, S. S.; Senthilguru, K.; Pramanik, K.; Banerjee, I.; Anis, Arfat; Al‐Zahrani, S. M.; Pal, Kunal
Abstract: Modulation of crystallization of stearic acid and its derivatives is important for tuning the properties of stearate oleogels. The present study delineates the crystallization of stearic acid in stearate oleogels in the presence of Span 60. Microarchitecture analysis revealed that stearic acid crystals in the oleogels changed its shape from plate‐like structure to a branched architecture in the presence of Span 60. Consequently, a significant variation in the mobility of the solute molecules inside the oleogel (Fluorescence recovery after photobleaching studies, FRAP analysis) was observed. Thermal analysis (gelation kinetics and DSC) revealed shortening of nucleation induction time and secondary crystallization with an increase in the Span 60 concentration. Furthermore, isosolid diagram suggested better physical stability of the formulations at higher proportions of Span 60. XRD analysis indicated that there was a decrease in the crystal size and the crystallinity of the stearic acid crystals with an increase in Span 60 concentration in the Span 60 containing oleogels. However, crystal growth orientation was unidirectional and found unaltered with Span 60 concentration (Avarmi analysis using DSC data). The mechanical study indicated a composition‐dependent variation in the viscoelastic properties (instantaneous [τ1 ], intermediate [τ2 ], and delayed [τ3 ] relaxation times) of the formulations. In conclusion, Span 60 can be used to alter the kinetics of the crystallization, crystal habit and crystal structure of stearic acid. This study provides a number of clues that could be used further for developing oleogel based formulation.